'Tax the rich'? The financial crisis, fiscal fairness, and progressive income taxation. Issue 3 (19th August 2019) - Limberg, Julian
Abstract: Has the financial crisis influenced taxes on the rich? In this article, I argue that crisis countries have raised income tax progressivity because of fiscal fairness considerations. I test this claim by analysing a new data set on top marginal personal income tax (PIT) rates for 122 countries from 2006 to 2014, applying matching methods and a difference-in-differences design. The results show that countries with a financial crisis have increased top PIT rates by 4 percentage points. Furthermore, rising public debt only leads to higher top PIT rates when it is crisis-induced. These findings demonstrate that notions of fiscal fairness can still shape progressive taxation in the 21st century.